Effects of Ce4+ and Cd2+ substitutions on superconducting fluctuation behavior, ultrasonic velocity and elastic properties of Fe-Doped (T1,Bi)-1212 high temperature superconductors / Shabani Ismail - Ismail, Shabani (2015)
In this study, two series of superconductor compounds with starting composition T10.9Bi0.1Sr2-xCexCa0.9Y0.1Cu1.99Fe0.01O7-o (x = 0—0.20) and T10.9Bi0.1Sr1.8Yb0.2Ca1.xCdxCu1.99Fe0.01O7-o (x - 0-0.4) ceramics were prepared using the conventional solid state synthesis method to elucidate their physical properties. For Ce-substituted of T10.9Bi0.1Sr2-xCexCa0.9Y0.1Cu1.99Fe0.01O7-o (x = 0—0.20) samples, the zero critical temperature, Tczero increased from 65.4 K (x = 0.05) to 71.0 K (x = 0.10), but slightly decreased for x > 0.10 indicating the optimum value of average copper valence was achieved at x = 0.10. Excess conductivity analysis using the Aslamazov Larkin, AL and Lawrence-Doniach, LD models revealed two dimensional, 2D to threedimensional, 3D transition of superconducting fluctuation behavior, SFB with the highest transition temperature, T2D-3D at x = 0.10. FTIR analysis in conjunction with XRD results showed softening of FeO2/CuO2 planar oxygen mode which is suggested to be related to possible increase of interplane coupling, J and this is supported by computed results based on the LD model. The enhanced J increases superconducting coherence length along c-axis, ^c(0), and hence lowers anisotropy, y resulting in enhanced superconducting properties. For T10.9Bi0.1Sr1.8Yb0.2Ca1.xCdxCu1.99Fe0.01O7-o (x - 0-0.4) ceramics, substitution of Cd caused Tc zero increasing from 40.0 K (x = 0) to 76.4 K (x = 0.3) before decreasing to 74.8 K (x = 0.4) with increasing Cd2+ contents. FTIR analysis in conjunction with XRD results indicates improved J that is evidenced in the form of decreased c-axis length and softening of the apical oxygen mode with Cd concentration. Excess conductivity analyses showed cross-over between 2D to 3D SFB transition for all the samples (x = 0.1-0.4) with the highest T2D-3D was observed at x = 0.3. Similar calculation revealed longest value of §c(0) and the highest J at x = 0.3. Ultrasonic velocity measurements was performed on longitudinal and shear velocities at 9 MHz in temperature ranges of 80-280 K and 80-220 K, respectively, for T10.9Bi0.1Sr1.8Yb0.2Ca1.xCdxCu1.99Fe0.01O7-o (x - 0-0.4) and T10.9Bi0.1Sr2-xCexCa0.9Y0.1Cu1.99Fe0.01O7-o (x = 0-0.20) ceramics to study the influence of Cd and Ce substitutions on elastic properties and elastic anomaly. For the former series, ultrasonic velocity measurements at 80 K showed a non-linear increase in both absolute longitudinal and shear velocities as well as elastic moduli with Cd substitution with the largest increase observed for the x = 0.3 sample. Temperature dependant longitudinal modulus showed elastic anomaly characterized by a step-like slope change at around 230 K for x = 0 & x = 0.3 and at around 250 K for x = 0.4 with the x = 0.3 sample showing the sharpest slope change. For T1.09Bi0.1Sr2-xCexCa0.9Y0.1Cu1.9 9Fe0.01O7.g series, Ce was observed to influence elastic moduli at 80K which showed the largest value obtained at x = 0.10. A longitudinal velocity anomaly was observed at around 260 K for the unsubstituted sample (x = 0). Ce substitution caused the temperature of the elastic anomaly to shift to 250 K (x = 0.1) and 262 K (x = 0.2). The existence of the step-like elastic anomaly was suggested to be due to oxygen ordering taking place in Tl-0 planes. The analysis of the elastic behavior in the vicinity of the elastic anomalies using Landau free-energy model for both T10.9Bi0.1Sr1.8Yb0.2Ca1.xCdxCu1.99Fe0.01O7-o (x - 0-0.4) and T10.9Bi0.1Sr2-xCexCa0.9Y0.1Cu1.99Fe0.01O7-o (x = 0-0.20) series suggests that the anomaly is due to a phase transition which involves oxygen ordering.